GLP-1 receptor agonists in Parkinson’s disease: an updated comprehensive systematic review with meta-analysis - Mohamed Mohsen Helal; Hala AbouShawareb; Omarfayez Hussein Abbas; Roaa Haddad; Youmna Zain; Ahmed S. A. Osman; Amr K. Hassan (Diabetology & Metabolic Syndrome)
Abstract Previous studies have demonstrated an increased risk of developing Parkinson’s disease (PD) in patients with type 2 diabetes mellitus (T2DM), as well as more severe and rapid motor and non-motor deterioration in diabetic PD patients compared to their non-diabetic counterparts. Additional research has suggested that diabetic subjects treated with glucagon-like peptide-1 (GLP-1) receptor agonists exhibit a reduced incidence of PD compared to those receiving other anti-diabetic medications. GLP-1 receptor agonists are FDA-approved therapies for T2DM, and recent studies have explored their potential as repurposed treatments for neurodegenerative diseases, including PD, AD, and ALS, as well as cerebrovascular disorders. This systematic review aims to assess the available literature on the efficacy and safety profiles of GLP-1 receptor agonists in PD management. A comprehensive search of PubMed, Scopus, CENTRAL, Web of Science, Embase, and ClinicalTrials.gov was conducted to identify relevant studies. The primary outcomes of this review include motor impairment in PD, as assessed by MDS-UPDRS Part III, as well as motor complications (Part IV) and motor experiences of daily living (Part II), and the incidence of gastrointestinal and systemic side effects. Meta-analysis showed that GLP-1 receptor agonists significantly improved motor function, as reflected by MDS-UPDRS Part III scores in the ON state (mean difference = − 2.88; p = 0.01; I2 = 30%), although they were associated with a higher incidence of adverse events across all safety outcomes. Findings and conclusions of this review will contribute to a clearer understanding of the therapeutic potential of GLP-1 receptor agonists in PD, guiding future clinical research and treatment strategies.